ARTIFICIAL INTELEGENCY UNTUK LAYANAN KESEHATAN DI PERPUSTAKAAN UNBRAH - Pero Hasfera, Imca (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2023)
Artificial intelligence is a field within computer science and engineering that refers to the ways in which machines can easily perform tasks that would normally require human intervention and human intelligence. Basically a machine can think for itself to do a task. Through artificial intelligence machines can perform complex or simple tasks with greater efficiency and higher speed than humans. AI is developing rapidly in the health sector, especially in treatment management and diagnosis. AI has created the sensation of artificial intelligence that goes beyond human tasks and abilities. Research results suggest that in the future, AI can support human judgment, aid in clinical decision-making, and improve treatment efficiency. The growth of AI in healthcare is related to the complexity of modern medicine, which requires vast amounts of information to analyze, and there is also a limited number of doctors to meet that need with human intelligence. Baiturrahmah University (UNBRAH) as one of the tertiary institutions engaged in the health sector and has the Siti Rahma Islamic Hospital and Dental and Oral Special Hospital, should have become a health information center for the community, especially for its library. The UNBRAH Library as a public service institution must provide excellent community services without differentiating one another. Through AI, excellent service programs, especially in the UNBRAH library, can be realized in the form of online health information services, according to the background by utilizing AI and applications, so that this service can become the identity of the UNBRAH library.